Simultaneous 2-photon calcium imaging at different cortical depths in vivo with spatiotemporal multiplexing - Cheng, Adrian (2011)
In vivo 2-photon calcium imaging would benefit from the use of multiple excitation beams to increase scanning speed, signal-to-noise ratio, field of view, or to image different axial planes simultaneously. We adapted a spatiotemporal multiplexing approach to circumvent the problem of light scattering ambiguity in deep tissue inherent to multifocal 2-photon microscopy. We demonstrate 2-photon calcium imaging at multiple axial planes in the in vivo mouse brain to monitor network activity of large ensembles of cortical neurons in three spatial dimensions.